Anti-fake injection magic hook belt and preparation method thereof
Patent Information
- Application Number
- CN202611017549.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]然而,在现有技术中,传统印刷工艺在魔术钩带表面的适配性较差,油墨附着力不足,容易出现脱落、磨损等问题,导致防伪标识失效;普通印刷图案主要以透视可见为主,反射辨识度低,在强光、弱光以及机器扫描环境下识别困难,无法满足快速准确的溯源需求;传统魔术钩带的成型工艺难以实现一面为规整蘑菇钩头、另一面为平整膜面的一体化结构,平整面的复合与印刷处理难度大,后续热熔胶贴合过程中容易污染印刷层,导致图案模糊、脱落;现有防伪魔术钩带的防伪层级较低,防伪标识单一易仿制,且功能单一,无法同时满足高端市场对防伪性、耐久性和附加功能的多重需求
[0023](1)将挤出温度下调并采用梯度控温,在模具工位增设预压与排气结构,同时采用分段缓慢冷却定型并降低牵引张力;将蘑菇钩头进行矮化处理,降低其高度并加宽根部,将顶面改为大曲率微弧面,同时将凹坑深度浅化并做圆角过渡,梯度控温与分段冷却有效降低了聚烯烃熔体的弹性模量,使分子链在冷却过程中有充足时间松弛,从而消除钩头根部的内应力集中;预压与排气结构避免了气泡缺陷,使钩头表面更加致密平整;矮化宽基的设计减小了钩面凹凸落差,浅化凹坑与圆角过渡则消除了积墨死角,钩面印刷时油墨分布均匀,无漏印、断墨现象,激光雕刻时不易打穿基材,印刷层在后续弯折中不易从根部开裂,相较于传统钩带因钩面不平、应力集中导致的印刷合格率低下问题,使防伪印刷工艺能够稳定连续进行,为大规模工业化生产奠定了可靠基础。
Smart Images

Figure CN122876785A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of anti-counterfeiting printing technology, and in particular to an anti-counterfeiting injection-molded magic hook tape and its preparation method. Background Technology
[0002] As a commonly used flexible connecting accessory, hook and loop fasteners have been widely applied in various fields such as clothing, footwear, bags, accessories, medical supplies, hygiene products, home textiles, and industrial fasteners, thanks to their convenient opening and closing characteristics, good adhesion, and wide material adaptability. They have become an indispensable part of modern industrial production and daily life. With the market's increasing awareness of product quality and brand protection, high-end brands, medical supplies, and special industrial products have placed higher demands on hook and loop fasteners. They not only need basic connecting functions but also reliable anti-counterfeiting and traceability capabilities to effectively combat counterfeit and substandard products and protect consumer rights and brand image.
[0003] To meet market demand for anti-counterfeiting features on hook straps, existing technologies primarily employ printing patterns or markings on the surface of the hook strap to achieve anti-counterfeiting purposes. Common printing methods include gravure printing, flexographic printing, digital inkjet printing, and laser engraving. Some technical solutions also attempt to improve the durability of anti-counterfeiting labels by adding a protective coating to the printed layer or by pre-printing anti-counterfeiting patterns on a functional film and then combining it with the hook strap. In addition, some technical solutions introduce various anti-counterfeiting elements such as invisible patterns and traceability codes to enhance the anti-counterfeiting effect.
[0004] However, in existing technologies, traditional printing processes have poor adaptability to the surface of magic hook straps, resulting in insufficient ink adhesion and easy problems such as peeling and wear, leading to the failure of anti-counterfeiting labels. Ordinary printed patterns are mainly visible through light, with low reflectivity, making identification difficult in strong light, low light, and machine scanning environments, and failing to meet the needs of rapid and accurate traceability. The molding process of traditional magic hook straps makes it difficult to achieve an integrated structure with a regular mushroom hook head on one side and a flat film surface on the other. The composite and printing processing of the flat surface is difficult, and the subsequent hot melt adhesive bonding process can easily contaminate the printed layer, resulting in blurred patterns and peeling. Existing anti-counterfeiting magic hook straps have a low level of anti-counterfeiting, and the anti-counterfeiting labels are simple and easy to counterfeit, and their functions are limited, failing to meet the multiple needs of the high-end market for anti-counterfeiting, durability, and additional functions. Summary of the Invention
[0005] This invention overcomes the shortcomings of the prior art and provides an anti-counterfeiting injection-molded magic hook tape and its preparation method.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a method for preparing an anti-counterfeiting injection-molded magic hook tape, comprising the following steps:
[0007] S1. Polyolefin resin is heated and melted, and then extruded to form a molten film. The molten film is then continuously molded to obtain a strip substrate. The heating and melting temperature is 185-205℃, and the continuous molding adopts a gradient cooling method.
[0008] S2. The strip substrate is subjected to segmented cooling and shaping treatment, and the traction tension is adjusted to obtain a dimensionally stable shaped substrate; wherein, the cooling adopts a three-stage cooling method, and the traction tension is controlled at 0.15-0.25MPa;
[0009] S3. Select the printing surface of the pre-treated substrate, apply a primer evenly, and then dry and cure it to obtain the pre-treated printing substrate; wherein, the drying temperature is 60-70℃.
[0010] S4. Print an anti-counterfeiting pattern on the pre-treated surface of the substrate to be printed to form an anti-counterfeiting printing layer, thereby obtaining a substrate with anti-counterfeiting markings; wherein, when the surface to be printed is a hook surface, a high-reflectivity system is used.
[0011] S5. The substrate with anti-counterfeiting mark is coated with a functional protective coating on the surface of the anti-counterfeiting printing layer and then cured to obtain a substrate to be cut after the functional coating is cured; wherein, the functional protective coating contains microcapsules.
[0012] S6. The substrate to be cut is cut and wound according to preset specifications to finally obtain anti-counterfeiting injection-molded magic hook tape.
[0013] In a preferred embodiment of the present invention, in step S1, the polyolefin resin is selected from polypropylene resin or polyethylene resin; the continuous molding process includes a mold forming station and a shaping station arranged sequentially.
[0014] In a preferred embodiment of the present invention, in step S1, the gradient cooling range is 195℃→160℃; the continuous molding process is to perform pre-pressing and venting processes in sequence, the pre-pressing temperature is 120-130℃, and the venting is achieved through a micro-channel of 0.05-0.1mm.
[0015] In a preferred embodiment of the present invention, in step S1, one side of the strip substrate is a uniformly distributed mushroom hook structure, i.e., a hook surface, and the other side is a flat film surface; the height of the mushroom hook is 0.5-0.7mm, and the root diameter is 0.7-0.9mm; the mushroom hook adopts a sparse-dense-sparse gradient arrangement, and the spacing between the arrangement varies from 1.2mm→0.8mm→1.2mm.
[0016] In a preferred embodiment of the present invention, the top surface of the mushroom hook head is a large curvature micro-arc surface with a curvature radius of 0.8-1.0 mm, and the top surface is provided with nanoscale directional stripe texture with a spacing of 5-10 μm; the depth of the pit between the hook heads is 0.2-0.3 mm, and the edge of the pit is provided with a rounded corner transition of R0.1 mm.
[0017] In a preferred embodiment of the present invention, in step S2, the temperature ranges of the three-stage cooling are 45℃→35℃→25℃ respectively.
[0018] In a preferred embodiment of the present invention, in step S3, the primer is a polyurethane resin or a chlorinated polypropylene resin, and its coating amount is 2-3 g / m2, which has the functions of enhancing ink adhesion, improving visual effect and preventing hot melt adhesive contamination.
[0019] In a preferred embodiment of the present invention, in step S4, the printing method used to print the anti-counterfeiting pattern is selected from one or more combinations of gravure printing, flexographic printing, digital inkjet printing, ultraviolet curable ink printing, transfer printing, laser engraving, laser marking, laser etching, embossing, and screen printing; the anti-counterfeiting pattern is selected from one or more combinations of QR code, barcode, anti-counterfeiting pattern, brand logo, invisible pattern, traceability code, laser microcode, and laser dark pattern.
[0020] In a preferred embodiment of the present invention, in step S5, the functional protective coating is an acrylic resin containing microcapsules; the microcapsules are microcapsules of fragrance or mosquito repellent agents; the curing is selected from low-temperature drying or ultraviolet curing, with ultraviolet curing using an energy of 800-1000 mJ / cm². 2 .
[0021] Secondly, the present invention provides an anti-counterfeiting injection-molded magic hook strap, characterized in that it is prepared by any one of the above-mentioned methods.
[0022] This invention addresses the shortcomings of the prior art and has the following beneficial effects:
[0023] (1) The extrusion temperature was lowered and gradient temperature control was adopted. A pre-compression and venting structure was added to the mold station. At the same time, segmented slow cooling and shaping were adopted and the traction tension was reduced. The mushroom hook head was shortened, its height was reduced and the root was widened. The top surface was changed to a large curvature micro-arc surface. At the same time, the depth of the pit was shallowed and rounded corners were made. Gradient temperature control and segmented cooling effectively reduced the elastic modulus of polyolefin melt, allowing the molecular chains sufficient time to relax during the cooling process, thereby eliminating the internal stress concentration at the root of the hook head. The pre-compression and venting structure The design avoids bubble defects, making the hook surface denser and smoother. The short and wide base design reduces the unevenness of the hook surface, and the shallow pits and rounded corners eliminate ink accumulation dead angles. During hook surface printing, the ink is evenly distributed, with no missing prints or ink breaks. Laser engraving is less likely to penetrate the substrate, and the printed layer is less likely to crack from the root during subsequent bending. Compared with the low printing pass rate caused by uneven hook surface and stress concentration in traditional hook straps, this design enables the anti-counterfeiting printing process to be carried out stably and continuously, laying a reliable foundation for large-scale industrial production.
[0024] (2) By combining the primer with the shallow pit structure and introducing a functional protective coating, the technical problems of hot melt adhesive contamination and insufficient durability of anti-counterfeiting labels are effectively solved. A primer coating with enhanced adhesion, visual enhancement and anti-hot melt adhesive contamination is applied before printing. At the same time, the depth of the pits between the hooks is shallowed and rounded edges are set. On the outer surface of the anti-counterfeiting printing layer, a transparent functional protective coating with built-in microcapsules is applied. The active groups in the primer coating can anchor the non-polar molecular chains on the surface of the polyolefin substrate to form a dense isolation layer. This isolation layer can effectively prevent the low molecular weight components in the subsequent hot melt adhesive from penetrating and migrating into the printing layer. The design of shallow pits and rounded corners makes The significantly reduced pit volume prevents hot melt adhesive from accumulating and stagnating within it. The base coating completely covers the inner wall of the pit, eliminating direct contact between adhesive residue and ink. The outer functional protective coating acts as a physical barrier, isolating it from external friction, moisture, and UV radiation. Its built-in microcapsules remain stably sealed under normal conditions, only rupturing to release fragrance or mosquito-repellent components upon friction, pressure, or temperature changes, thus combining protection and triggering functions. Compared to existing technologies where anti-counterfeiting patterns are easily corroded, blurred, or detached by hot melt adhesive, this technology provides multiple layers of protection from bottom isolation to surface protection, significantly extending the lifespan of the anti-counterfeiting label. It also adds functionality to the magic hook strap, achieving a deep integration of anti-counterfeiting and functionality. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 This is a flowchart of a preferred embodiment of the present invention. Detailed Implementation
[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein. Therefore, the scope of protection of the invention is not limited to the specific embodiments disclosed below.
[0029] Application Overview:
[0030] To improve the compatibility of traditional hook and loop fasteners in terms of anti-counterfeiting functions and structural performance, some studies have attempted to directly apply advanced anti-counterfeiting technologies such as high-reflectivity ink printing and laser engraving to the surface of existing hook and loop fasteners. However, the inherent structure of traditional mushroom-head hook and loop fasteners has the following problems: First, the dome-shaped hook head structure with deep recesses results in a large difference in the printed surface height, causing ink accumulation, ink breaks, and inconsistent reflection, making scanning and identification difficult. Second, stress concentration at the root of the hook head makes the printed layer prone to cracking and peeling off at the root during subsequent bending. Third, the deep recesses retain hot melt adhesive, which can corrode the ink and obscure the anti-counterfeiting pattern. Fourth, the top of the hook head is too thin and the recesses are too deep, making it easy to penetrate the substrate or cause the hook head to break during laser engraving. These obstacles make it impossible to achieve industrial application of a simple printing + hook and loop superposition scheme.
[0031] The applicant discovered that the root of the problem lies not in the printing technology itself, but in the fundamental mismatch between the microstructure of the hook and tape substrate and its molding process and printing requirements. Therefore, the solution must shift from making printing adapt to the hook surface to making the hook surface actively adapt to printing. If the extrusion molding process and the geometry of the mushroom hook can be systematically and collaboratively adjusted to give the hook surface a smoother, shallower, rounder, and more reflective properties, not only can traditional printing obstacles be eliminated, but it can also form a positive synergistic amplification effect with anti-counterfeiting technologies such as high-reflective inks and laser engraving. In other words, the structure itself becomes part of the anti-counterfeiting system, rather than a burden.
[0032] The applicant proposed that, in terms of extrusion process, internal stress was eliminated and hook surface flatness was improved by lowering and gradually controlling the extrusion temperature, adding pre-compression and venting structures at the mold station, adopting segmented slow cooling and shaping, and reducing traction tension. In terms of mushroom hook head structure, modifications were made to shorten, round, shallow pit, and micro-texturize: the hook head height was reduced and the root was widened to eliminate stress concentration; the top surface was changed to a large-curvature micro-arc surface and nano-level directional stripes were added to enhance directional reflection and ink-locking ability; the pit depth was shallowed and rounded to prevent dirt accumulation; and a gradually varying density arrangement was adopted to form an invisible anti-counterfeiting texture. Through the deep integration of these processes and structures, the hook surface was transformed from difficult to print to easy to print and with built-in anti-counterfeiting features, ultimately achieving a comprehensive improvement in printing pass rate, anti-counterfeiting level, and service life.
[0033] like Figure 1 As shown, a method for preparing an anti-counterfeiting injection-molded magic hook tape includes the following steps:
[0034] S1. Polyolefin resin is heated and melted, and then extruded to form a molten film. The molten film is then continuously molded to obtain a strip substrate. The heating and melting temperature is 185-205℃, and the continuous molding adopts a gradient cooling method.
[0035] S2. The strip substrate is subjected to segmented cooling and shaping treatment, and the traction tension is adjusted to obtain a dimensionally stable shaped substrate; wherein, the cooling adopts a three-stage cooling method, and the traction tension is controlled at 0.15-0.25MPa;
[0036] S3. Select the printing surface of the pre-treated substrate, apply a primer evenly, and then dry and cure it to obtain the pre-treated printing substrate; wherein, the drying temperature is 60-70℃.
[0037] S4. Print an anti-counterfeiting pattern on the pre-treated surface of the substrate to be printed to form an anti-counterfeiting printing layer, thereby obtaining a substrate with anti-counterfeiting markings; wherein, when the surface to be printed is a hook surface, a high-reflectivity system is used.
[0038] S5. The substrate with anti-counterfeiting mark is coated with a functional protective coating on the surface of the anti-counterfeiting printing layer and then cured to obtain a substrate to be cut after the functional coating is cured; wherein, the functional protective coating contains microcapsules.
[0039] S6. The substrate to be cut is cut and wound according to preset specifications to finally obtain anti-counterfeiting injection-molded magic hook tape.
[0040] The core innovation of this invention lies in moving beyond the traditional approach of merely optimizing the printing process. It involves a systematic and coordinated adjustment of both the extrusion molding process and the microstructure of the mushroom hook. In terms of process, gradient temperature control, pre-pressure venting, segmented slow cooling, and reduced traction tension eliminate internal stress at the hook root and improve hook surface flatness. Structurally, the mushroom hook is dwarfed, rounded, has shallow pits, and undergoes nanoscale directional texture modification, employing a gradient arrangement of density. This deep integration of process and structure transforms the hook surface from a surface unsuitable for printing into an easy-to-print and self-contained anti-counterfeiting carrier with multiple anti-counterfeiting features. This effectively solves the technical obstacles of traditional magic hook tapes when integrating high-reflectivity printing and laser anti-counterfeiting, such as ink accumulation, cracking, contamination, and substrate penetration.
[0041] Each step will be explained in detail below.
[0042] In step S1, the polyolefin resin is heated to a molten state and extruded to form a molten film. The molten film is then continuously formed through a mold forming station and a shaping station set in sequence to obtain a strip substrate with a uniformly distributed mushroom hook structure on one side and a flat film surface on the other side.
[0043] The polyolefin resin is selected from polypropylene resin or polyethylene resin, and the heating and melting temperature is 185-205℃.
[0044] The continuous forming process employs a gradient cooling method, allowing the molecular chains of the melt sufficient time to relax during the cooling process, thereby eliminating the internal stress concentration at the root of the hook head. The gradient cooling range is 195℃→160℃, with a linear cooling rate of 1.5-2.5℃ / min.
[0045] Pre-pressing and venting are performed sequentially at the mold forming station. Pre-pressing ensures that the melt fills the cavity, while venting removes residual gas and prevents bubble defects from forming on the hook surface.
[0046] The pre-compression temperature is 120-130℃, the pre-compression pressure is 0.3-0.6MPa, and the pressurization duration is 2-5s. Exhaust is achieved through tiny channels opened at the bottom of the cavity, with a channel diameter of 0.05-0.1mm. Each hook cavity has 4-8 channels, which are evenly distributed.
[0047] The formed mushroom hook head adopts a short and wide base design to reduce the unevenness of the hook surface and facilitate subsequent printing; the hook head height is 0.5-0.7mm and the root diameter is 0.7-0.9mm.
[0048] The top surface of the hook is designed with a large curvature micro-arc surface and adds nano-level directional stripe texture to enhance directional reflection capability and provide ink-locking structure.
[0049] The top surface has a curvature radius of 0.8-1.0 mm, and the nanoscale directional stripe texture is formed by etching the top surface of the mold cavity with a femtosecond laser. The etching depth is 0.3-0.8 μm, the stripe spacing is 5-10 μm, and the stripes are oriented along the length of the hook.
[0050] The recesses between the hooks are made shallower and rounded to eliminate ink buildup and prevent hot melt adhesive from lingering. The recesses are 0.2-0.3mm deep and have rounded edges with an radius of 0.1mm.
[0051] The mushroom-shaped hook head adopts a sparse-dense-sparse gradient arrangement to form an invisible anti-counterfeiting texture on the hook surface. The gradient cycle consists of 10-15 rows of hook heads, with the spacing between the rows gradually changing from 1.2mm to 0.8mm and then back to 1.2mm within the cycle. Multiple cycles are repeated along the length of the hook tape.
[0052] In step S2, the formed strip substrate is subjected to a three-stage cooling and shaping process. Each stage has a constant temperature dwell time to ensure that the substrate cools down at a uniform speed and fully releases thermal stress, resulting in a dimensionally stable shaped substrate.
[0053] The three-stage cooling system has temperature ranges of 45℃, 35℃, and 25℃, with a constant temperature residence time of 8-15 minutes for each stage. The cooling method is air cooling with a wind speed of 0.5-1.2 m / s.
[0054] At the same time, the traction tension is adjusted, and a lower tension is used in conjunction with slow cooling to ensure that the molecular chains are fully relaxed and to prevent residual stress at the root of the hook from causing subsequent bending and cracking; the traction tension is controlled at 0.15-0.25MPa.
[0055] In step S3, the surface to be printed on the substrate is selected and pre-treated to improve the surface tension of the substrate and ensure that the primer is evenly spread and firmly anchored.
[0056] The surface pretreatment method is selected from corona treatment or plasma treatment; when using corona treatment, the power density is 100-200 W·min / m². 2 When plasma treatment is used, the treatment gas is air or nitrogen; after pretreatment, the surface tension of the substrate to be printed reaches 42-48 mN / m.
[0057] After pretreatment, a primer is applied evenly. The active groups in the primer anchor the molecular chains on the activated substrate surface, forming a dense isolation layer.
[0058] The primer is made of polyurethane resin or chlorinated polypropylene resin, and the coating method is roller coating or spray coating, with a coating amount of 2-3 g / m². 2 .
[0059] After coating, the substrate is sent into the drying tunnel for drying and curing to obtain a pre-treated substrate ready for printing; the drying temperature is 60-70℃ and the drying time is 3-8 minutes.
[0060] The primer has a triple function of enhancing ink adhesion, improving visual appeal, and preventing hot melt adhesive contamination. Combined with the shallow design and rounded corners of the hook recess, the primer can completely cover the inner wall of the recess, eliminating dead corners where hot melt adhesive can remain and effectively preventing the low molecular weight components of hot melt adhesive from penetrating and migrating into the printing layer during subsequent lamination processes.
[0061] In step S4, anti-counterfeiting patterns are printed on the pre-treated substrate to form an anti-counterfeiting printing layer, resulting in a substrate with anti-counterfeiting markings.
[0062] The printing method used to print the anti-counterfeiting pattern is selected from one or more combinations of gravure printing, flexographic printing, digital inkjet printing, ultraviolet curing ink printing, transfer printing, laser engraving, laser marking, laser etching, embossing, and screen printing; the anti-counterfeiting pattern is selected from one or more combinations of QR code, barcode, anti-counterfeiting pattern, brand logo, invisible pattern, traceability code, laser microcode, and laser dark pattern.
[0063] When the surface to be printed is the hook surface, a high-reflectivity system is used for printing. The high-reflectivity ink, combined with the large curvature micro-arc surface and nano-level directional stripe texture of the hook head, can form a directional reflection signal with strong consistency and high recognition, which can be quickly and accurately read in strong light, weak light and machine scanning environments.
[0064] Among them, the high-reflectivity ink is an ink containing aluminum powder or pearlescent pigment; when aluminum powder is used, the particle size of aluminum powder is 5-15μm, and the amount added is 8-20% of the total mass of ink; when pearlescent pigment is used, the particle size of pearlescent pigment is 10-30μm, and the amount added is 15-25% of the total mass of ink.
[0065] When the surface to be printed is a flat film surface, a conventional printing system is used.
[0066] The shallow recesses and rounded corners ensure even ink distribution, preventing ink gaps or breaks. During laser engraving, the hook tip is less likely to penetrate the substrate, ensuring the anti-counterfeiting pattern remains intact and clear.
[0067] In step S5, a functional protective coating is applied to the surface of the anti-counterfeiting printing layer. The protective coating acts as a physical barrier to isolate the anti-counterfeiting printing layer from external friction, moisture and ultraviolet rays. The functional protective coating is made of acrylic resin and is applied by roller coating or spraying, with a dry film thickness of 5-15 μm.
[0068] The coating contains microcapsules that are stably sealed under normal conditions. When exposed to friction, pressure, or temperature changes, the microcapsules rupture and release the core material components, giving the magic hook a trigger-activated additional function.
[0069] The microcapsule wall material is melamine-formaldehyde resin or polyurethane, the microcapsule particle size is 10-30μm, the core material is fragrance factor or mosquito repellent factor, and the amount of microcapsule added is 3-8% of the coating solid content; low-pressure spraying or low-speed roller coating is used in the coating process, and the coating pressure does not exceed 0.2MPa to avoid microcapsule rupture.
[0070] After coating, a curing process is performed. After curing, the protective coating, primer, and printing layer form a composite protective system, achieving multiple protections for the anti-counterfeiting printing layer from bottom isolation to surface protection.
[0071] The curing method is selected from low-temperature drying or ultraviolet curing; when using low-temperature drying, the drying temperature is 70-90℃ and the drying time is 10-20 minutes; when using ultraviolet curing, the ultraviolet energy is 800-1000 mJ / cm². 2 The irradiation time is 3-8 seconds.
[0072] In step S6, the substrate to be cut after the functional coating has been cured is cut according to the preset specifications, and then wound up to finally obtain the anti-counterfeiting injection-molded magic hook tape; wherein, the cutting accuracy is controlled within ±0.5mm and the winding tension is 0.05-0.15MPa.
[0073] The resulting magic hook tape has one side as an integrated mushroom hook surface or a flat film surface with an anti-counterfeiting printing layer and a protective coating. The hook surface has a regular structure, clear and firm printed patterns, and has reliable adhesion, multiple anti-counterfeiting traceability capabilities, and trigger-type additional functions. It is suitable for anti-counterfeiting packaging and connection applications for high-end brands, medical consumables, and special industrial products.
[0074] To further simplify and make the present invention achieve its objectives and effects, the present invention will be further illustrated in conjunction with the following specific embodiments and comparative examples, but the present invention is not limited to the scope of the embodiments described herein.
[0075] It should be noted that the raw materials used in the examples and comparative examples are described below:
[0076] Polypropylene resin: VA content 28.0wt%, melt index 400g / 10min, purchased from Shanghai Wangtao Technology Co., Ltd.
[0077] Polyethylene resin: 99% purity, purchased from Zibo Mantanghong Trade Co., Ltd.
[0078] Polyurethane resin: 100% content, solids content 30±1%, grade FS-1930C, purchased from Anhui Feimiao Chemical Co., Ltd.
[0079] Chlorinated polypropylene resin: 100% content, viscosity 350-500, purchased from Nanjing Youao Chemical Co., Ltd.
[0080] Acrylic resin: 99% content, molecular weight approximately 2500-20000, purchased from Yingde Xinlian Chemical Co., Ltd.
[0081] Melamine-formaldehyde resin: CAS number 9003-08-1, density 1.13-1.14 g / cm³ 3 Purchased from Jiangsu Pulesi Biotechnology Co., Ltd.
[0082] Fragrance factor: content is 99%, purchased from Changzhou Youfang New Material Technology Co., Ltd.
[0083] Mosquito repellent agent: 30% content, model PBS271, purchased from Shanghai Hete Chemical Co., Ltd.
[0084] Example 1:
[0085] S1. Polypropylene resin is heated to 195℃ and melted, then extruded to form a molten film. The molten film is continuously formed through a mold forming station and a shaping station. Gradual cooling is used to reduce the temperature from 195℃ to 160℃ at a rate of 2.0℃ / min. Pre-pressing and venting are performed at the mold forming station. The pre-pressing temperature is 125℃, the pressure is 0.45MPa, and the time is 3.5s. The venting channel diameter is 0.075mm, and each hook cavity has 6 channels. The mushroom hook height is 0.6mm, the root diameter is 0.8mm, the top surface curvature radius is 0.9mm, the top surface stripe spacing is 7.5μm, the pit depth is 0.25mm, the pit edge radius is R0.1mm, and the hook arrangement cycle is 12 rows with the arrangement spacing gradually changing from 1.2mm to 0.8mm to 1.2mm.
[0086] S2. The strip substrate is cooled and shaped in three stages at temperatures of 45℃, 35℃ and 25℃ respectively, with each stage held at a constant temperature for 11.5 minutes. Air cooling is used with a wind speed of 0.85m / s and a traction tension of 0.2MPa to obtain the shaped substrate.
[0087] S3. Perform corona treatment on the printing surface of the shaped substrate at a power density of 150 W·min / m². 2After treatment, the surface tension is 45 mN / m. A polyurethane primer is applied with a coating amount of 2.5 g / m², and the substrate is dried at 65°C for 5.5 min to obtain the substrate to be printed.
[0088] S4. Print anti-counterfeiting patterns on the pre-treated surface of the substrate to be printed. Use a combination of gravure printing and laser engraving. The patterns are QR codes and laser microcodes. The high-reflective ink contains aluminum powder with a particle size of 10μm and an addition amount of 14%, resulting in a substrate with anti-counterfeiting labels.
[0089] S5. Apply an acrylic resin protective coating to the surface of the anti-counterfeiting printing layer. The coating contains microcapsules with melamine-formaldehyde resin as the wall material and fragrance factor as the core material. The microcapsule particle size is 20μm and the addition amount is 5.5% of the coating solid content. Low-pressure spraying is used with a pressure of 0.1MPa and a dry film thickness of 10μm. UV curing is used with an energy of 900mj / cm² and a time of 5.5s to obtain the substrate to be cut.
[0090] S6. Cut the substrate to be cut according to the preset specifications, with the cutting accuracy controlled within ±0.5mm and the winding tension at 0.1MPa, to obtain the anti-counterfeiting injection-molded magic hook tape.
[0091] Example 2:
[0092] This embodiment is basically the same as Embodiment 1, except that the polyolefin resin in S1 is different. Specifically, in step S1, the polypropylene resin is replaced with polyethylene resin.
[0093] Example 3:
[0094] This embodiment is basically the same as embodiment 1, except that the primer in S3 is different. Specifically, in step S3, the polyurethane resin primer is replaced with chlorinated polypropylene resin primer, while the coating amount and drying conditions remain unchanged.
[0095] Example 4:
[0096] This embodiment is basically the same as embodiment 1, except that the microcapsule core material in S5 is different. Specifically, in step S5, the fragrance factor is replaced with a mosquito repellent factor, while the other parameters remain unchanged.
[0097] Example 5:
[0098] This embodiment is basically the same as embodiment 1, except that the curing method in S5 is different. Specifically, in step S5, ultraviolet curing is changed to low-temperature drying, the drying temperature is 80°C and the drying time is 15 minutes, and the other parameters remain unchanged.
[0099] Example 6:
[0100] This embodiment is basically the same as embodiment 1, except that the cooling rate in S1 is taken as the minimum value of the interval, specifically: in step S1, the cooling rate is changed to 1.5℃ / min.
[0101] Example 7:
[0102] This embodiment is basically the same as embodiment 1, except that the cooling rate in S1 is the maximum value of the interval, specifically: in step S1, the cooling rate is changed to 2.5℃ / min.
[0103] Example 8:
[0104] This embodiment is basically the same as embodiment 1, except that the diameter of the exhaust channel in S1 is taken as the minimum value of the range, specifically: in step S1, the diameter of the exhaust channel is changed to 0.05mm.
[0105] Example 9:
[0106] This embodiment is basically the same as embodiment 1, except that: the diameter of the exhaust channel in S1 is taken as the maximum value of the range, specifically: in step S1, the diameter of the exhaust channel is changed to 0.1mm.
[0107] Example 10:
[0108] This embodiment is basically the same as embodiment 1, except that the top surface stripe spacing in S1 is taken as the minimum value of the interval, specifically: in step S1, the top surface stripe spacing is changed to 5μm.
[0109] Example 11:
[0110] This embodiment is basically the same as embodiment 1, except that the top surface stripe spacing in S1 is taken as the maximum value of the interval, specifically: in step S1, the top surface stripe spacing is changed to 10μm.
[0111] Example 12:
[0112] This embodiment is basically the same as embodiment 1, except that: the constant temperature time for each segment of the three-stage cooling in S2 is taken as the minimum value of the interval. Specifically, in step S2, the constant temperature dwell time for each segment is changed to 8 minutes.
[0113] Example 13:
[0114] This embodiment is basically the same as embodiment 1, except that: the constant temperature time for each segment of the three-stage cooling in S2 is taken as the maximum value of the interval. Specifically, in step S2, the constant temperature dwell time for each segment is changed to 15 minutes.
[0115] Example 14:
[0116] This embodiment is basically the same as embodiment 1, except that the traction tension in S2 is taken as the minimum value of the range, specifically: in step S2, the traction tension is changed to 0.15MPa.
[0117] Example 15:
[0118] This embodiment is basically the same as embodiment 1, except that the traction tension in S2 is taken as the maximum value of the range, specifically: in step S2, the traction tension is changed to 0.25MPa.
[0119] Comparative Example 1:
[0120] This comparative example is basically the same as Example 1, except that it uses the traditional magic hook strap manufacturing process, without gradient cooling, pre-pressure venting, segmented cooling, high traction tension, non-shortening of the hook head, deep pit, no primer, and no protective coating. The specific steps are as follows:
[0121] S1. Polypropylene resin is heated to 210℃ and melted, then extruded through casting to form a molten film. It is directly formed through a mold forming station and cooled naturally without pre-pressing or venting. The mushroom hook head height is 1.0mm, the root diameter is 0.5mm, the top surface is a normal arc surface without stripes, the pit depth is 0.5mm, the pit edge has no rounded corners, and the hook heads are evenly arranged with a spacing of 1.0mm.
[0122] S2. The strip substrate is rapidly cooled by water, with the temperature dropping directly from 45℃ to 25℃ without segmented constant temperature. The traction tension is 0.4MPa, resulting in a shaped substrate.
[0123] S3. No corona treatment is applied to the shaped substrate, and no primer is applied; it is used directly as the substrate to be printed.
[0124] S4. Print anti-counterfeiting patterns on the surface of the substrate to be printed, using ordinary ink and conventional printing.
[0125] S5. No functional protective coating applied;
[0126] S6. Cut and roll up according to preset specifications to obtain magic hook tape.
[0127] Comparative Example 2:
[0128] This comparative example is basically the same as Example 1, except that the pre-compression and venting treatment in S1 are omitted. The specific steps of S1 are as follows: polypropylene resin is heated to 195°C to melt and then extruded to form a molten film. The molten film is continuously formed through the mold forming station and the shaping station. The temperature is gradually reduced from 195°C to 160°C at a rate of 2.0°C / min. No pre-compression and venting treatment are performed at the mold forming station. The mushroom hook height is 0.6 mm, the root diameter is 0.8 mm, the top surface curvature radius is 0.9 mm, the top surface stripe spacing is 7.5 μm, the pit depth is 0.25 mm, the pit edge radius is R0.1 mm, the hook arrangement period is 12 rows, and the arrangement spacing gradually changes from 1.2 mm to 0.8 mm to 1.2 mm.
[0129] Comparative Example 3:
[0130] This comparative example is basically the same as Example 1, except that the three-stage cooling in S2 is omitted and replaced with natural cooling. The specific steps of S2 are: the strip substrate is naturally cooled to room temperature without controlling the cooling rate and the constant temperature time, and the traction tension is 0.2 MPa to obtain the shaped substrate.
[0131] Comparative Example 4:
[0132] This comparative example is basically the same as Example 1, except that the primer coating in S3 is omitted. The specific steps of S3 are: corona treatment of the printing surface of the shaped substrate with a power density of 150 W·min / m 2 After treatment, the surface tension is 45mN / m. No primer is applied, and the substrate to be printed is obtained directly.
[0133] Comparative Example 5:
[0134] This comparative example is basically the same as Example 1, except that the functional protective coating in S5 is omitted. The specific steps of S5 are: the anti-counterfeiting printing layer is not coated with a protective coating and is directly used as the substrate to be cut.
[0135] Comparative Example 6:
[0136] This comparative example is basically the same as Example 1, except that the cooling rate in S1 is lower than the minimum value in the range. The specific steps of S1 are as follows: polypropylene resin is heated to 195°C to melt and then extruded to form a molten film. The molten film is continuously formed through the mold forming station and the shaping station. Gradual cooling is used to reduce the temperature from 195°C to 160°C at a cooling rate of 1.0°C / min. Pre-pressing and venting are performed at the mold forming station. The pre-pressing temperature is 125°C, the pressure is 0.45MPa, and the time is 3.5s. The diameter of the venting channel is 0.075mm, and each hook cavity is provided with 6 channels. The height of the mushroom hook is 0.6mm, the root diameter is 0.8mm, the top surface curvature radius is 0.9mm, the top surface stripe spacing is 7.5μm, the pit depth is 0.25mm, the pit edge radius is R0.1mm, and the hook arrangement cycle is 12 rows with the arrangement spacing gradually changing from 1.2mm to 0.8mm to 1.2mm.
[0137] Comparative Example 7:
[0138] This comparative example is basically the same as Example 1, except that the cooling rate in S1 is higher than the maximum value in the range. The specific steps of S1 are as follows: the polypropylene resin is heated to 195°C to melt and then extruded to form a molten film. The molten film is continuously formed through the mold forming station and the shaping station. The temperature is reduced from 195°C to 160°C using a gradient cooling method, with a cooling rate of 3.0°C / min. The rest are the same as the steps in S1 of Comparative Example 6.
[0139] Comparative Example 8:
[0140] This comparative example is basically the same as Example 1, except that the diameter of the exhaust channel in S1 is lower than the minimum value of the range. The specific steps of S1 are as follows: the polypropylene resin is heated to 195°C to melt and then extruded to form a molten film. The molten film is continuously formed through the mold forming station and the shaping station. The temperature is reduced from 195°C to 160°C using a gradient cooling method at a rate of 2.0°C / min. Pre-compression and venting are performed at the mold forming station. The pre-compression temperature is 125°C, the pressure is 0.45MPa, and the time is 3.5s. The diameter of the exhaust channel is 0.04mm, and 6 channels are set in each hook cavity. The other hook parameters are the same as those of Comparative Example 6.
[0141] Comparative Example 9:
[0142] This comparative example is basically the same as Example 1, except that the diameter of the exhaust channel in S1 is higher than the maximum value in the range. The specific steps of S1 are as follows: the polypropylene resin is heated to 195°C to melt and then extruded to form a molten film. The molten film is continuously formed through the mold forming station and the shaping station. The temperature is reduced from 195°C to 160°C using a gradient cooling method at a rate of 2.0°C / min. Pre-pressing and venting are performed at the mold forming station. The pre-pressing temperature is 125°C, the pressure is 0.45MPa, and the time is 3.5s. The diameter of the exhaust channel is 0.11mm, and each hook cavity is provided with 6 channels. The other hook parameters are the same as those of Comparative Example 6.
[0143] Comparative Example 10:
[0144] This comparative example is basically the same as Example 1, except that the spacing of the top surface stripes in S1 is lower than the minimum value of the interval. The specific steps of S1 are as follows: polypropylene resin is heated to 195°C to melt and then extruded to form a molten film. The molten film is continuously formed through the mold forming station and the shaping station. The temperature is gradually reduced from 195°C to 160°C at a rate of 2.0°C / min. Pre-pressing and venting are performed at the mold forming station. The pre-pressing temperature is 125°C, the pressure is 0.45MPa, and the time is 3.5s. The diameter of the venting channel is 0.075mm, and each hook cavity has 6 channels. The height of the mushroom hook is 0.6mm, the root diameter is 0.8mm, the top surface curvature radius is 0.9mm, the top surface stripe spacing is 4μm, the pit depth is 0.25mm, the pit edge radius is R0.1mm, the hook arrangement cycle is 12 rows, and the arrangement spacing gradually changes from 1.2mm to 0.8mm to 1.2mm.
[0145] Comparative Example 11:
[0146] This comparative example is basically the same as Example 1, except that the spacing of the top surface stripes in S1 is higher than the maximum value of the interval. The specific steps of S1 are as follows: polypropylene resin is heated to 195°C to melt and then extruded to form a molten film. The molten film is continuously formed through the mold forming station and the shaping station. The temperature is gradually reduced from 195°C to 160°C at a rate of 2.0°C / min. Pre-pressing and venting are performed at the mold forming station. The pre-pressing temperature is 125°C, the pressure is 0.45MPa, and the time is 3.5s. The diameter of the venting channel is 0.075mm, and each hook cavity has 6 channels. The height of the mushroom hook is 0.6mm, the root diameter is 0.8mm, the top surface curvature radius is 0.9mm, the top surface stripe spacing is 11μm, the pit depth is 0.25mm, the pit edge radius is R0.1mm, the hook arrangement cycle is 12 rows, and the arrangement spacing gradually changes from 1.2mm to 0.8mm to 1.2mm.
[0147] Comparative Example 12:
[0148] This comparative example is basically the same as Example 1, except that the constant temperature dwell time in S2 is lower than the minimum value of the interval. The specific steps of S2 are as follows: the strip substrate is cooled and shaped in three stages, with temperatures of 45°C, 35°C and 25°C in sequence, and each stage is kept at a constant temperature for 5 minutes. Air cooling is used with a wind speed of 0.85 m / s and a traction tension of 0.2 MPa to obtain the shaped substrate.
[0149] Comparative Example 13:
[0150] This comparative example is basically the same as Example 1, except that the constant temperature dwell time in S2 is higher than the maximum value of the interval. The specific steps of S2 are as follows: the strip substrate is cooled and shaped in three stages, with temperatures of 45°C, 35°C and 25°C in sequence, and each stage is kept at a constant temperature for 18 minutes. Air cooling is used with a wind speed of 0.85 m / s and a traction tension of 0.2 MPa to obtain the shaped substrate.
[0151] Comparative Example 14:
[0152] This comparative example is basically the same as Example 1, except that the traction tension in S2 is lower than the minimum value of the interval. The specific steps of S2 are as follows: the strip substrate is cooled and shaped in three stages, with temperatures of 45°C, 35°C and 25°C in sequence, and each stage is kept at a constant temperature for 11.5 minutes. Air cooling is used with a wind speed of 0.85 m / s and a traction tension of 0.1 MPa to obtain the shaped substrate.
[0153] Comparative Example 15:
[0154] This comparative example is basically the same as Example 1, except that the traction tension in S2 is higher than the maximum value in the interval. The specific steps of S2 are as follows: the strip substrate is cooled and shaped in three stages, with temperatures of 45°C, 35°C and 25°C in sequence, and each stage is kept at a constant temperature for 11.5 minutes. Air cooling is used with a wind speed of 0.85 m / s and a traction tension of 0.3 MPa to obtain the shaped substrate.
[0155] Performance testing: The anti-counterfeiting injection-molded magic hook tapes obtained in Examples 1-15 and Comparative Examples 1-15 were subjected to performance tests in sequence for ink layer adhesion, directional reflection recognition rate, hot melt adhesive contamination resistance, laser engraving critical energy density, and microcapsule trigger release efficiency. The results are shown in Table 1.
[0156] Printed ink adhesion: A 200mm long sample with a width equal to the full width of the hook tape was cut from the hook tape to be tested. Three different locations were selected on the printed area of the hook surface, and a peel test was performed using 3M 600 tape. The tape was applied to the printed pattern surface with constant pressure, and after pressing for 5 seconds, the tape was rapidly peeled off at a 180° angle and a speed of 300mm / min. The proportion of the peeled area of the printed pattern to the total area of the test area was observed and recorded. The test was repeated three times at each location, and the average value was recorded as the result. Printing ink adhesion
[0157] Calculate using the following formula:
[0158] ;
[0159] The unit is a percentage, and the recognition rate is calculated under three different lighting conditions. This value reflects the directional reflection effect produced by the synergistic effect of high-reflectivity ink, the large curvature micro-arc surface of the hook head, and the nano-level directional stripe texture. The higher the value, the stronger the readability of the anti-counterfeiting pattern under complex lighting conditions.
[0160] Directional reflection recognition rate: The sample was placed in a standard light source box, and three illumination conditions were set: strong light (10000 lux), weak light (50 lux), and 850nm infrared supplementary light simulating a barcode scanning environment. A fixed QR code scanner with a resolution of 1280×1024 was used to read the anti-counterfeiting pattern printed on the hook surface. Under each illumination condition, 50 consecutive scans were performed, and the number of successful decodings was recorded. Directional reflection recognition rate. Calculate using the following formula:
[0161] ;
[0162] The unit is a percentage, and the recognition rate is calculated under three different lighting conditions. This value reflects the directional reflection effect produced by the synergistic effect of high-reflectivity ink, the large curvature micro-arc surface of the hook head, and the nano-level directional stripe texture. The higher the value, the stronger the readability of the anti-counterfeiting pattern under complex lighting conditions.
[0163] Hot melt adhesive contamination resistance: The printed surface of the Velcro strap was hot-pressed with a 0.1mm thick EVA-based hot melt adhesive film at 120℃ and 0.3MPa pressure for 3 seconds. After cooling, the hot melt adhesive film was carefully peeled off. The surface of the printed pattern was observed using an optical microscope at 100x magnification. The percentage of the total printed area where the pattern was blurred, discolored, or missing due to hot melt adhesive residue or penetration was recorded as follows: Simultaneously, Fourier transform infrared spectroscopy was used to test the surface of the printed layer at 1730 cm⁻¹. -1 The absorption intensity of the carbonyl characteristic peak at the point was calculated using the blank printed layer without the composite hot melt adhesive film as a reference to determine the increase in absorption intensity. Hot melt adhesive contamination resistance Calculate using the following formula:
[0164] ;
[0165] in The absorption intensity is used as a reference sample, and the calculated result is in percentage form. This value comprehensively characterizes the ability of the primer isolation layer and shallow pit structure to block the penetration of low molecular weight components of hot melt adhesive. The higher the value, the less likely the anti-counterfeiting pattern is to be contaminated in subsequent lamination processes.
[0166] Critical energy density for laser engraving: A nanosecond pulsed laser marking machine with a wavelength of 1064 nm and a pulse width of 100 ns was used to engrave the hook surface of the sample. The laser power started from 2 W and increased in increments of 0.5 W to 10 W. A 5 mm × 5 mm square area was engraved at each power point, and the scanning speed was fixed at 200 mm / s. After engraving, the hook morphology of each area was observed using a scanning electron microscope, and the minimum laser power at which melting collapse, perforation, or breakage occurred at the top of the hook was recorded. Simultaneously, the etching depth of the anti-counterfeiting pattern formed by laser etching was measured. The ratio of the laser engraving depth to the design depth; the critical energy density for laser engraving. Calculate using the following formula:
[0167] ;
[0168] in The scanning speed is 200 mm / s. The laser pulse repetition period is calculated in J / cm². 2 This value reflects the tolerance of the hook head to laser engraving after the hook head is dwarfed, the base is wide, and the top surface curvature is optimized. The higher the value, the clearer the laser anti-counterfeiting mark can be obtained without damaging the hook head structure.
[0169] Microcapsule-triggered release efficacy: A Velcro strap sample coated with a functional protective layer was cut into 20mm × 20mm pieces and placed in a sealed transparent test vial. The sample surface was rubbed repeatedly for 30 seconds using a friction tester at a load of 500g and a frequency of 60 cycles / min, or the sample was placed in a 40℃ constant temperature oven for 10 minutes to trigger microcapsule rupture. Immediately after friction or heating, headspace solid-phase microextraction-gas chromatography-mass spectrometry was used to collect headspace gas in the test vial to detect the concentration of characteristic components of the core material. The fragrance factor was detected by characteristic peaks, and the mosquito-repellent factor was detected by active ingredients. An untreated original sample was used as a blank control. Microcapsule-triggered release efficacy. Calculate using the following formula:
[0170] ;
[0171] in The concentration of the characteristic component measured after triggering. The concentration of the blank control is... The total concentration theoretically released after complete rupture of microcapsules of equal mass is determined in advance using ultrasonic disruption. The calculation result is expressed as a percentage, which characterizes the response sensitivity and release effect of microcapsules in the protective coating under mechanical friction or temperature changes. A higher value indicates a more significant triggering of fragrance or mosquito-repellent functions.
[0172] Table 1: Performance test results of anti-counterfeiting injection-molded magic hooks in Examples 1-15 and Comparative Examples 1-15
[0173] Group Printing ink adhesion (%) Oriented reflection recognition rate (%) Hot melt adhesive contamination resistance (%) <![CDATA[Critical energy density for laser engraving J / cm 2 > Microcapsule-triggered release efficacy (%) Example 1 98.5 98.5 94.6 2.45 86.3 Example 2 97.8 97.9 93.9 2.40 85.7 Example 3 97.9 98.1 94.1 2.42 85.9 Example 4 98.4 98.4 94.5 2.44 86.5 Example 5 98.2 98.2 94.3 2.43 85.1 Example 6 97.5 97.7 93.5 2.38 85.3 Example 7 97.6 97.8 93.6 2.39 85.4 Example 8 98.0 98.2 94.0 2.41 86.0 Example 9 98.1 98.2 94.0 2.41 86.0 Example 10 98.6 98.7 94.7 2.46 86.4 Example 11 98.3 98.2 94.2 2.42 86.1 Example 12 97.7 97.8 93.7 2.39 85.5 Example 13 97.9 97.9 93.8 2.40 85.6 Example 14 97.8 97.8 93.6 2.38 85.4 Example 15 97.6 97.8 93.5 2.37 85.3 Comparative Example 1 42.3 45.2 23.4 0.85 0.0 Comparative Example 2 68.5 64.9 58.3 1.45 72.4 Comparative Example 3 71.2 68.0 61.5 1.52 74.1 Comparative Example 4 85.6 88.7 38.9 2.10 80.5 Comparative Example 5 90.3 90.9 85.7 2.25 0.0 Comparative Example 6 85.2 86.1 82.4 2.05 82.3 Comparative Example 7 86.7 87.6 83.1 2.08 82.9 Comparative Example 8 87.5 88.3 83.5 2.12 83.2 Comparative Example 9 87.3 88.1 83.4 2.11 83.1 Comparative Example 10 88.1 89.4 84.2 2.15 83.8 Comparative Example 11 87.8 88.9 83.9 2.13 83.5 Comparative Example 12 84.5 85.5 81.8 2.02 81.9 Comparative Example 13 84.9 85.8 82.1 2.03 82.1 Comparative Example 14 83.8 84.8 81.2 1.98 81.5 Comparative Example 15 85.9 86.9 82.8 2.07 82.6
[0174] A comparison of Example 1 and Comparative Example 1 reveals that: Comparative Example 1 employs a traditional process without gradient cooling, pre-pressure venting, or segmented cooling. The traction tension is 0.4 MPa, the hook height is 1.0 mm, the root diameter is 0.5 mm, the pit depth is 0.5 mm, and there are no rounded corners, primer, or protective coating. Under rapid cooling conditions after melt extrusion, the polyolefin molecular chains are frozen in a highly oriented, non-equilibrium state, resulting in significant residual internal stress at the hook root. A significant geometric difference exists between the deep pit and the pointed hook, preventing uniform ink spread and allowing only physical adhesion to the surface. During laser engraving, the release of internal stress easily leads to brittle breakage or melt-through of the hook. Low-molecular-weight plasticizers and non-crystallized components in the hot melt adhesive penetrate along the deep pits into the ink layer, swelling and damaging the ink resin. The microcapsules, lacking a protective coating, cannot stably exist on the hook surface. Therefore, the performance of Comparative Example 1 is significantly lower than that of Example 1.
[0175] A comparison of Example 1 and Comparative Example 2 reveals that: Comparative Example 2 omits pre-compression and venting treatments, while remaining identical to Example 1; in Example 1, pre-compression at 125°C ensures the melt is fully compacted before filling the cavity, promoting uniform molecular chain orientation; a venting channel with a diameter of 0.075 mm removes residual gas from the cavity; in Comparative Example 2, the melt is prone to entraining gas and forming microbubbles or voids when rapidly filling the hook cavity; these defects become stress concentration points after cooling, disrupting the continuity and density of the hook surface, leading to decreased ink adhesion, and preferential melting or cracking at defective areas during laser engraving; therefore, the ink layer adhesion of Comparative Example 2 is 68.5%, and the critical energy density for laser engraving is 1.45 J / cm². 2 All were lower than those in Example 1.
[0176] A comparison of Example 1 and Comparative Example 3 reveals that: Comparative Example 3 replaced the three-stage cooling with natural cooling, while remaining the same as Example 1; In Example 1, the segmented constant temperature of 45℃→35℃→25℃ provides a near-equilibrium thermodynamic path for the transformation of polypropylene molecular chains from the molten state to the crystalline state, allowing the molecular chains to fully relax and form a perfect lattice, thus releasing internal stress; The natural cooling rate is uneven, with a large difference between the cooling rate of the substrate surface and the interior, resulting in insufficient relaxation time for the molecular chains, causing uneven shrinkage and thermal stress, and residual orientation stress at the root of the hook; This stress causes the printed layer to easily crack from the root when bent, and reduces the geometrical accuracy of the hook, affecting the consistency of reflection; Therefore, the directional reflection recognition rate of Comparative Example 3 is 68.0%, which is lower than that of Example 1.
[0177] A comparison of Example 1 and Comparative Example 4 reveals that: Comparative Example 4 omits the primer coating, while remaining identical to Example 1; the polyurethane primer in Example 1, with a coating amount of 2.5 g / m², forms a dense isolation layer by hydrogen bonding or chemical bonding between the urethane groups on its molecular chain and the carbonyl and hydroxyl groups formed on the surface of the corona-treated polyolefin, resulting in a dense isolation layer; in Comparative Example 4, the ink and the polyolefin substrate are only physically bonded, lacking chemical anchoring; low molecular weight components in the hot melt adhesive, such as wax and oligomers, can directly penetrate the amorphous region of the polyolefin and come into contact with the ink, causing the ink to swell or dissolve; therefore, the hot melt adhesive contamination resistance of Comparative Example 4 is 38.9%, far lower than the 94.6% of Example 1.
[0178] A comparison of Example 1 and Comparative Example 5 reveals that: Comparative Example 5 omits the functional protective coating, while remaining identical to Example 1; the acrylic protective coating in Example 1 forms a cross-linked network, acting as a physical barrier to isolate external friction, moisture, and ultraviolet rays, and anchoring the microcapsules; the protective coating and the primer constitute a multi-layered protective structure, enhancing the overall durability of the anti-counterfeiting layer; in Comparative Example 5, the anti-counterfeiting printing layer is directly exposed, and the microcapsules, lacking a stable carrier, cannot be effectively fixed, easily rupturing or falling off due to friction or environmental factors, resulting in a 0% trigger release efficiency; the ink layer is easily scratched and worn; therefore, the microcapsule trigger release efficiency in Comparative Example 5 is 0%, and the adhesion of the printed ink layer also decreases to 90.3%.
[0179] A comparison of Examples 1 and Examples 2-5 reveals that: in Example 2, polypropylene resin was replaced with polyethylene resin; in Example 3, the primer was replaced with chlorinated polypropylene resin; in Example 4, the microcapsule core material was replaced with mosquito repellent agent; and in Example 5, ultraviolet curing was replaced with low-temperature drying. All of these substitutions fall within the preferred range defined by this invention. Polyethylene and polypropylene both belong to polyolefins and have similar non-polar chemical inertness. Chlorinated polypropylene has a similar structure to polypropylene, follows the principle of "like dissolves like," and has excellent anchoring effect. The microencapsulation and release mechanisms of the fragrance agent and the mosquito repellent agent are consistent. Both low-temperature drying and ultraviolet curing can fully crosslink the acrylic resin. Therefore, the properties of Examples 2-5 are highly similar to those of Example 1, verifying the universality of the technical solution.
[0180] A comparison of Examples 1 / 6-7 with Comparative Examples 6-7 reveals the following: Example 1 had a cooling rate of 2.0℃ / min, Example 6 had a rate of 1.5℃ / min, and Example 7 had a rate of 2.5℃ / min; Comparative Example 6 had a cooling rate of 1.0℃ / min, and Comparative Example 7 had a rate of 3.0℃ / min. A suitable cooling rate allows the molecular chains to relax and arrange themselves in an orderly manner simultaneously. In Comparative Example 6, the rate was too low, causing the melt to remain in the high-temperature zone for too long, potentially leading to thermo-oxidative degradation, a decrease in molecular weight, and reduced mechanical properties. In Comparative Example 7, the rate was too high, causing molecular chain relaxation to lag behind cooling, resulting in a large number of chain segments being locked in a non-equilibrium extension state, forming a highly oriented, high-stress structure, increasing the brittleness of the hook, making the printed layer prone to cracking, and making stress release during laser engraving more likely to cause damage. Therefore, the critical energy densities for laser engraving in Comparative Examples 6 and 7 are 2.05 and 2.08 J / cm³, respectively. 2 It is lower than 2.45 J / cm in Example 1. 2 .
[0181] A comparison of Examples 1 / 8-9 with Comparative Examples 8-9 reveals that: the exhaust channel diameter in Example 1 is 0.075 mm, in Example 8 it is 0.05 mm, and in Example 9 it is 0.10 mm; the diameter in Comparative Example 8 is 0.04 mm, and in Comparative Example 9 it is 0.11 mm. A channel with a diameter of 0.075 mm can effectively exhaust gas under pre-pressure without melt leakage. In Comparative Example 8, the channel is too small, resulting in high gas exhaust resistance and easy residue formation at the top of the hook, which becomes the origin of stress cracking and ink peeling. In Comparative Example 9, the channel is too large, causing melt to be squeezed into the channel under pressure, forming microburrs. These burrs damage the surface smoothness of the hook, affecting printing uniformity and directional reflection effects; the root of the burrs is also a potential stress concentration point. Therefore, the ink layer adhesion of Comparative Examples 8 and 9 is 87.5% and 87.3%, respectively, both lower than the 98.5% of Example 1.
[0182] A comparison of Examples 1 / 10-11 with Comparative Examples 10-11 reveals the following: Example 1 has a stripe spacing of 7.5 μm, Example 10 has 5 μm, and Example 11 has 10 μm; Comparative Example 10 has a spacing of 4 μm, and Comparative Example 11 has a spacing of 11 μm. The 7.5 μm spacing of the nanoscale stripes matches the particle size (10 μm) of the aluminum powder in the high-reflectivity ink, guiding the aluminum powder to arrange itself regularly and forming efficient directional reflection. The stripes in Comparative Example 10 are too dense, increasing processing difficulty and potentially causing excessive ink locking due to capillary action, affecting drying and reflection consistency. The stripes in Comparative Example 11 are too sparse, weakening the guiding effect on the aluminum powder arrangement, resulting in a more chaotic reflective surface and reduced ink anchoring. Therefore, the directional reflection recognition rates of Comparative Examples 10 and 11 are 89.4% and 88.9%, respectively, lower than the 98.5% of Example 1.
[0183] A comparison of Examples 1 / 12-13 with Comparative Examples 12-13 reveals the following: Example 1 had a constant temperature dwell time of 11.5 min per segment, Example 12 had 8 min, and Example 13 had 15 min; Comparative Example 12 had a dwell time of 5 min, and Comparative Example 13 had 18 min. A dwell time of 11.5 min allowed for sufficient temperature equilibrium within the substrate, uniform heat dissipation, and adequate time for creep relaxation of the molecular chains. Comparative Example 12 had a shorter dwell time, resulting in insufficient heat dissipation and a still relatively high internal temperature, leading to new thermal stress during subsequent cooling. Comparative Example 13 had a longer dwell time, causing excessive residence of the substrate in the low-temperature zone, potentially inducing secondary crystallization or crystal maturation, resulting in increased hardness and brittleness, decreased toughness, and reduced fatigue resistance of the hook. Therefore, the ink adhesion of Comparative Examples 12 and 13 was 84.5% and 84.9%, respectively, lower than that of Example 1.
[0184] A comparison of Examples 1 / 14-15 and Comparative Examples 14-15 reveals the following: Example 1 has a traction tension of 0.2 MPa, Example 14 has 0.15 MPa, and Example 15 has 0.25 MPa; Comparative Example 14 has a tension of 0.1 MPa, and Comparative Example 15 has 0.3 MPa. A tension of 0.2 MPa matches the segmented cooling, providing stable support without hindering molecular chain relaxation. In Comparative Example 14, the tension is too low, resulting in insufficient constraint on the substrate during cooling shrinkage, leading to uneven shrinkage in the width direction and warping or wrinkling. In Comparative Example 15, the tension is too high, applying excessive tensile stress before the substrate is fully cured, forcing the molecular chains to be highly oriented along the traction direction. This orientation stress is frozen in the finished product, superimposed on the cooling shrinkage stress, increasing the stress level at the hook root and making it prone to cracking during bending. Therefore, the critical energy densities for laser engraving in Comparative Examples 14 and 15 are 1.98 and 2.07 J / cm², respectively. 2 It is lower than 2.45 J / cm in Example 1. 2 .
[0185] Based on the preferred embodiments of the present invention described above, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A method for preparing an anti-counterfeiting injection-molded magic hook tape, characterized in that, Includes the following steps: S1. Polyolefin resin is heated and melted, and then extruded to form a molten film. The molten film is then continuously molded to obtain a strip substrate. The heating and melting temperature is 185-205℃, and the continuous molding adopts a gradient cooling method. S2. The strip substrate is subjected to segmented cooling and shaping treatment, and the traction tension is adjusted to obtain a dimensionally stable shaped substrate; wherein, the cooling adopts a three-stage cooling method, and the traction tension is controlled at 0.15-0.25MPa; S3. Select the printing surface of the pre-treated substrate, apply a primer evenly, and then dry and cure it to obtain the pre-treated printing substrate; wherein, the drying temperature is 60-70℃. S4. Print an anti-counterfeiting pattern on the pre-treated surface of the substrate to be printed to form an anti-counterfeiting printing layer, thereby obtaining a substrate with anti-counterfeiting markings; wherein, when the surface to be printed is a hook surface, a high-reflectivity system is used. S5. The substrate with anti-counterfeiting mark is coated with a functional protective coating on the surface of the anti-counterfeiting printing layer and then cured to obtain a substrate to be cut after the functional coating is cured; wherein, the functional protective coating contains microcapsules. S6. The substrate to be cut is cut and wound according to preset specifications to finally obtain anti-counterfeiting injection-molded magic hook tape.
2. The method for preparing an anti-counterfeiting injection-molded magic hook tape according to claim 1, characterized in that: In step S1, the polyolefin resin is selected from polypropylene resin or polyethylene resin; the continuous molding process includes a mold forming station and a shaping station arranged sequentially.
3. The method for preparing an anti-counterfeiting injection-molded magic hook tape according to claim 1, characterized in that: In step S1, the gradient cooling range is 195℃→160℃; the continuous molding process involves sequential pre-pressing and venting, with the pre-pressing temperature at 120-130℃ and venting achieved through micro-channels of 0.05-0.1mm.
4. The method for preparing an anti-counterfeiting injection-molded magic hook tape according to claim 1, characterized in that: In step S1, one side of the strip substrate is a uniformly distributed mushroom hook structure, i.e., a hook surface, and the other side is a flat film surface; the height of the mushroom hook is 0.5-0.7mm, and the root diameter is 0.7-0.9mm; the mushroom hook adopts a sparse-dense-sparse gradient arrangement, and the spacing between the arrangement varies from 1.2mm→0.8mm→1.2mm.
5. The method for preparing an anti-counterfeiting injection-molded magic hook tape according to claim 4, characterized in that: The top surface of the mushroom hook head is a large curvature micro-arc surface with a curvature radius of 0.8-1.0mm, and the top surface is provided with nano-level directional stripe texture with a spacing of 5-10μm; the depth of the pit between the hook heads is 0.2-0.3mm, and the edge of the pit is provided with a rounded transition of R0.1mm.
6. The method for preparing an anti-counterfeiting injection-molded magic hook tape according to claim 1, characterized in that: In step S2, the temperature ranges for the three-stage cooling process are 45℃→35℃→25℃ respectively.
7. The method for preparing an anti-counterfeiting injection-molded magic hook tape according to claim 1, characterized in that: In step S3, the primer is polyurethane resin or chlorinated polypropylene resin, and its coating amount is 2-3 g / m². 2 It combines the functions of enhancing ink adhesion, improving visual appeal, and preventing hot melt adhesive contamination.
8. The method for preparing an anti-counterfeiting injection-molded magic hook tape according to claim 1, characterized in that: In step S4, the printing method used to print the anti-counterfeiting pattern is selected from one or more combinations of gravure printing, flexographic printing, digital inkjet printing, ultraviolet curing ink printing, transfer printing, laser engraving, laser marking, laser etching, embossing, and screen printing; the anti-counterfeiting pattern is selected from one or more combinations of QR code, barcode, anti-counterfeiting pattern, brand logo, invisible pattern, traceability code, laser microcode, and laser dark pattern.
9. The method for preparing an anti-counterfeiting injection-molded magic hook tape according to claim 1, characterized in that: In step S5, the functional protective coating is an acrylic resin containing microcapsules; the microcapsules are microcapsules of fragrance or mosquito-repellent agents; the curing process is selected from low-temperature drying or ultraviolet curing, with ultraviolet curing using an energy of 800-1000 mJ / cm². 2 .
10. A counterfeit-proof injection-molded magic hook strap, characterized in that: It is prepared by any one of the following methods: anti-counterfeiting injection-molded magic hook tape according to claims 1-9.